Characterization of Acute HCV Infection and Transmission Networks in People Who Currently Inject Drugs in Catalonia: Usefulness of Dried Blood Spots. Issue 2 (25th August 2021) - Antuori, Adrián; Montoya, Vincent; Piñeyro, David; Sumoy, Lauro; Joy, Jeffrey; Krajden, Mel; González‐Gómez, Sara; Folch, Cinta; Casabona, Jordi; Matas, Lurdes; Colom, Joan; Saludes, Verónica; et al.
Abstract : Background and Aims: Accurate identification of recent HCV infections is critical for tracing the extent and mechanisms of ongoing transmission. We aimed to validate dried blood spot (DBS) samples for the assessment of Hepatitis C virus (HCV) genetic diversity and to determine epidemiological parameters including incidence, determinants of acute infection, and phylogenetic clustering in people who inject drugs (PWID). Approach and Results: HCV nonstructural protein 5B next‐generation sequencing was performed from plasma and/or DBS in 220 viremic PWID from the HepC detect II study. No significant differences were found in consensus sequences or Shannon entropy (SE) intrahost diversity estimate between paired plasma/DBS specimens. SE values were used to identify acute infections with 93.3% sensitivity (95% CI, 0.81–1.06) and 95.0% specificity (95% CI, 0.88–1.02) in a set of well‐defined controls. An acute HCV infection (either primary infection or reinfection) was detected in 13.5% of viremic participants and was associated with age ≤30 years (OR, 8.09), injecting less than daily (OR, 4.35), ≤5 years of injected drug use (OR, 3.43), sharing cocaine snorting straws (OR, 2.89), and being unaware of their HCV status (OR, 3.62). Annualized HCV incidence was estimated between 31 and 59/100 person‐years. On phylogenetic analysis, 46.8% of viremic cases were part of a transmission pair or cluster; age ≤30 years (OR, 6.16), acute infection (OR, 5.73), and infection with subtype 1a (OR, 4.78) were independently associated with this condition. Conclusions: The results obtained from plasma and DBS characterize PWID with acute infection and those involved in ongoing HCV transmission and allow estimating incidence from cross‐sectional data. This information is critical for the design and assessment of targeted harm reduction programs and test‐and‐treat interventions and to facilitate monitoring of HCV elimination in this key population.